From Transactions to Subscriptions: Customer Adoption, Organizational Readiness, and Business Model Innovation in an Emerging-Market Pet Retailer - Rima Rupita (Journal of Consumer Studies and Applied Marketing, 2026)
Subscription-based business models offer retailers an opportunity to replace episodic transactions with more predictable and enduring customer relationships. However, their implementation requires alignment between customer acceptance and organizational readiness. This study examines how a subscription model can be designed and implemented in an Indonesian multi-branch pet retailer operating in an emerging-market context. An interpretivist qualitative case study was conducted using two parallel interview strands involving 21 customers and nine employees across managerial and frontline roles. The interviews were supported by internal business documents, industry reports, a working subscription-platform prototype, and direct observation of competing retailers. The findings show that customer willingness to subscribe is driven by convenience, automated replenishment, personalization, and reduced stock-out risk, but remains conditional on transparent pricing, flexible modification, easy cancellation, and confidence in service delivery. Organizationally, the retailer possesses a viable recurring-demand base, branch infrastructure, service capabilities, and existing digital channels, yet remains only partially ready because of weaknesses in stock coordination, delivery scheduling, and subscription-specific processes. Fulfilment reliability emerged as the central mechanism linking customer adoption with organizational readiness, as the perceived value of a subscription depends on the retailer's ability to deliver recurring promises consistently. The study further identifies bounded flexibility as a key design principle, in which customers retain meaningful control over quantities, schedules, and cancellations within standardized operational limits. Accordingly, the proposed model combines customizable subscription packages, tiered pricing, scheduled delivery, loyalty incentives, and phased digital implementation. This study contributes to subscription business model research by conceptualizing viability as an alignment outcome between customer-side acceptance and organizational execution, rather than as a consequence of adoption intention alone. It also provides context-sensitive insights into subscription-based transformation in emerging-market specialty retail.